2017
DOI: 10.1002/cbic.201700596
|View full text |Cite
|
Sign up to set email alerts
|

A Multiperspective Approach to Solvent Regulation of Enzymatic Activity: HMG‐CoA Reductase

Abstract: 3-Hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase was investigated in different organic cosolvents by means of kinetic and calorimetric measurements, molecular dynamics simulations, and small-angle X-ray scattering. The combined experimental and theoretical techniques were essential to complement each other's limitations in the investigation of the complex interaction pattern between the enzyme, different solvent types, and concentrations. In this way, the underlying mechanisms for the loss of enzyme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To extract structural information about the sample, suitable models have to be assumed and adapted to match the recorded data. Typical experiments for SAXS are the elucidation of protein structures in solution ( Zhang et al, 2007 ; Dirkmann et al, 2018 ; Hura et al, 2019 ), macromolecules in solution ( Brosey and Tainer, 2019 ; Franke and Svergun, 2020 ) and in situ SAXS analysis of growth of silver nanoparticles ( Garcia et al, 2020 ), in situ SAXS analysis of growth kinetics of gold nanoparticles ( Chen et al, 2021 )in solutions. While it is also possible to measure more complicated hetereogeneous systems with SAXS, the interpretation of the data becomes increasingly difficult.…”
Section: Introductionmentioning
confidence: 99%
“…To extract structural information about the sample, suitable models have to be assumed and adapted to match the recorded data. Typical experiments for SAXS are the elucidation of protein structures in solution ( Zhang et al, 2007 ; Dirkmann et al, 2018 ; Hura et al, 2019 ), macromolecules in solution ( Brosey and Tainer, 2019 ; Franke and Svergun, 2020 ) and in situ SAXS analysis of growth of silver nanoparticles ( Garcia et al, 2020 ), in situ SAXS analysis of growth kinetics of gold nanoparticles ( Chen et al, 2021 )in solutions. While it is also possible to measure more complicated hetereogeneous systems with SAXS, the interpretation of the data becomes increasingly difficult.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the effects of organic co‐solvents on enzyme activity and stability depend on the chemical and physicochemical properties of OS and the type of enzyme [31] . Interactions between an enzyme and an OS can result in molecular changes in the enzyme structure, such as loss of structural water, changes in its flexibility and conformational alterations [32–34] . OS molecules may also act as enzyme inhibitors [35] .…”
Section: Introductionmentioning
confidence: 99%
“…[31] Interactions between an enzyme and an OS can result in molecular changes in the enzyme structure, such as loss of structural water, changes in its flexibility and conformational alterations. [32][33][34] OS molecules may also act as enzyme inhibitors. [35] In general, enzymes are more tolerant to hydrophobic OSs than hydrophilic ones as the latter can cause destructive structural changes due to easier penetration into the enzyme and greater capacity to replace structural water within the enzyme hydration shell.…”
Section: Introductionmentioning
confidence: 99%